2020
DOI: 10.1158/1541-7786.mcr-19-0759
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Zebrafish Model of Metastasis Identifies the HSD11β1 Inhibitor Adrenosterone as a Suppressor of Epithelial–Mesenchymal Transition and Metastatic Dissemination

Abstract: Metastasis of cancer cells is multi-step process and dissemination is an initial step. Here we report a tamoxifen-controllable Twist1a-ERT2 transgenic zebrafish line as a new animal model for metastasis research, and demonstrate that this model can serve as a novel platform for discovery of antimetastasis drugs targeting metastatic dissemination of cancer cells. By crossing Twist1a-ERT2 with xmrk (a homolog of hyperactive form of EGFR) transgenic zebrafish, which develops hepatocellular carcinoma, approximatel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Epiboly progression was affected more severely when embryos were treated with 50 μM concentration (Figure 1A, Supplementary Figure 1E and Supplementary Table 2). Among the epiboly-interrupting drugs, Adrenosterone, Zardaverine, Racecadotril and Disulfiram have already been reported to inhibit metastasis-related molecular mechanisms (10-13). This evidence supports that epiboly-interrupting drugs have the potential to suppress metastasis of human cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Epiboly progression was affected more severely when embryos were treated with 50 μM concentration (Figure 1A, Supplementary Figure 1E and Supplementary Table 2). Among the epiboly-interrupting drugs, Adrenosterone, Zardaverine, Racecadotril and Disulfiram have already been reported to inhibit metastasis-related molecular mechanisms (10-13). This evidence supports that epiboly-interrupting drugs have the potential to suppress metastasis of human cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression of the transcription factor, Twist, a regulator of EMT, occurs in metastatic human HCC samples and correlates with decreased E-cadherin expression [ 148 ]. Inhibition of hydroxysteroid (11-beta) dehydrogenase1 (HSD11b1), a prognostic biomarker of human HCC, in crosses between the tamoxifen-controllable Twist1a-ERT2 and Xmrk transgenic HCC zebrafish, suppressed the metastasis of transplanted human cell lines and led to recovered E-cadherin expression via Snail and Slug transcription factor signaling [ 149 , 150 ]. E-cadherin can bind to EGFR and regulate its activation leading to either anti- or pro-tumorigenic outcomes depending on the stage of HCC progression and the status of Wnt/β-catenin signaling [ 151 ].…”
Section: Xmrk In Fish Models Of Hepatocellular Carcinomamentioning
confidence: 99%
“…Another study used a cross between a tamoxifen-controlled Twist1a-ERT2 transgenic zebrafish line and an Xmrk transgenic zebrafish that develops metastatic HCC to screen chemotherapy drugs. They found that the drugs adrenosterone, rabeprazole, and olmesartan, suppressed the metastasis of transplanted human liver cancer cells [ 150 ]. Adrenosterone is an inhibitor of hydroxysteroid (11-beta) dehydrogenase 1, which is highly expressed in metastatic HCC, rabeprazole acts to block hydrogen/potassium-transporting ATPase, and olmesartan prevents the action of angiotensin 2 types 1 receptor, which promotes metastasis progression [ 150 ].…”
Section: Translational Xmrk Studiesmentioning
confidence: 99%
“…Hence, using a tissue-specific promoter and a LBD fusion protein, two levels of regulation, spatial and temporal are combined in a single transgene to achieve oncogene activity control. In another work, Joji Nakayama, Zhiyuan Gong and colleagues described a transgenic zebrafish line expressing a Twist1a-ER T2 fusion driven by the liver-specific promoter fapb10 together with the xmrk oncogene under the control of the Tet-ON system as a model for metastatic dissemination of liver cancer cells induced by both 4-OHT and Dox [ 210 ]. This possibility to activate simultaneously or sequentially different cancer genes confers a huge flexibility to the transgenic zebrafish cancer model.…”
Section: Transgenesismentioning
confidence: 99%